Cyclodextrin polymers: Structure, synthesis, and use as drug carriers. (July 2021) - Liu, Zongjian; Ye, Lin; Xi, Jianing; Wang, Jin; Feng, Zeng-guo
Abstract: Cyclodextrin-based polymers (CDPs) are amphiphilic macromolecules owing to their unique structure and the presence of multiple hydroxyl groups. These polymers have become increasingly popular in applications ranging from biomedicine to environmental science. In this review, four types of CDPs are distinguished based on their structural characteristics: cyclodextrin-based polyrotaxanes, grafted cyclodextrin polymers, cross-linked cyclodextrin polymers, and cyclodextrin-originated star/multi-arm polymers. The discussion includes the syntheses and properties of several derivatives of CDPs. In addition to low toxicity, good bioavailability and biodegradability, and the feasibility of inclusion complexation and chemical modification of cyclodextrins, these polymers have prominent advantages, such as stimuli responsiveness and the ability to form well-defined aggregated nanostructures, which make them promising candidates for applications related to controlled and targeted drug delivery. In this review, we have highlighted the evolution, unique types, and properties of various CDPs, which are core aspects that differ from previously published reviews. Additionally, the synergistic effect of cyclodextrin and cross-linking monomers, as well as their use as drug carriers over the past decade, have been emphasized. Graphical abstract: Image, graphical abstract